Medications in Bronchospasm and Asthma among the Critically Ill Patients: A Drug Utilization Study from Southern India (Nepal Journal of Epidemiology, 2011)
Objective: Critically ill patients are prone for altered reactivity of the airway and drug therapy has pivotal role in the management of bronchospasm. The objective of the study was to evaluate the prescribing patterns and adverse effects of therapeutic agents for bronchospasm and asthma in the medical ICU.Methods: A prospective observational study was carried out among inpatients of the medical ICU receiving drugs for bronchospasm and asthma.Results: 220 patients received drugs for bronchospasm and asthma. Male preponderance was noticed (60.5%). Salbutamol (R03AC02) 92.7% was the most common bronchodilator prescribed. Ipratropium plus salbutamol (R03AK04) 55.5% was most frequently used bronchodilator combination. All bronchodilators were administered by inhalational route (nebulization) except methylxanthines Conclusion: Utilization patterns of drugs for bronchospasm and asthma were in concordance with treatment guidelines.Key words: Bronchospasm; Asthma; Southern IndiaDOI: http://dx.doi.org/10.3126/nje.v1i2.5136 Nepal Journal of Epidemiology 2011;1 (2):57-59